Immunization strategies against respiratory syncytial virus in Panama: considerations for decision-making in a tropical country—a working group meeting report - Sáez-Llorens, Xavier; Castillo, Catherine Lissette; Franco, Danilo; Esquivel, Raúl; Luciani, Kathia; DeAntonio, Rodrigo (Frontiers in Public Health, 2025)
Following the approval of the respiratory syncytial virus (RSV) vaccine and a new monoclonal antibody for passive immunization in children, some Latin American countries have begun using both strategies to prevent RSV-disease. We reviewed these strategies to generate recommendations for their implementation in the Republic of Panama. Experts from different areas and health institutions in Panama gathered in an academic working group to discuss epidemiological data, safety and efficacy aspects, and health economic evaluation elements for both strategies. Aspects of implementing new strategies in Panama were addressed, considering the implementation risks, target population, acceptability, resources, equity, programmatic feasibility, and impact evaluation. According to experts, passive immunization must be universal, including children not exposed to their first RSV season. It could be flexible according to seasonality and must be performed at birth while other vaccines are administered. The immunization must be performed outside the Expanded Program on Immunization (EPI). Maternal vaccination targets all children whose mothers are eligible for vaccination and could receive it within the recommended gestational age (32 weeks) as per the World Health Organization and Pan American Health Organization recommendations. A specific RSV surveillance must be implemented in Panama to measure the impact of the strategy implemented. Likewise, an economic evaluation should be performed to define the cost-effectiveness of these strategies. An education campaign and dissemination of the intervention of the population through healthcare professionals is recommended.